Letramento digital na conjuntura da pandemia: - SILVA, Clorisneia Soares Vila Nova. (2024)
This paper aimed to investigate the digital literacies of kindergarten and elementary school teachers in the municipal teaching network of Araguaína-TO in the context of the pandemic, considering the use of digital technologies in the teaching and learning process and its implications in the lives of teachers. The dissertation is grounded in the field of Applied Linguistics and in the perspective of literacy studies. Well as, in-depth knowledge of digital technologies is part of digital literacy, Kleiman (1995), Buzato (2007) and Soares (2002) conceptualize digital literacy as the social practices that are intertwined and modified with digital technologies. This is a qualitative field research with an interpretativist and exploratory approach, based on Flick (2009). To treat the data we will use the content analysis technique (BARDIN, 2016). The data were collected between the months of November and December 2022 by means of an online semi- structured questionnaire, hosted on the Google Forms platform, containing 24 questions, 21 of which were multiple choice and 3 with short answers. In addition, another resource used to validate the research was an on-site interview in which the researcher visited in person some teaching institutions in the municipal network of Araguaína-TO to verify the data with some teachers who participated in the research. In all, 171 educators participated in the research, 96.5% female teachers and 3.5% male teachers, 62% from early childhood education centers and 37% from elementary I schools. It is believed that this research presented significant results for the area of applied linguistics and literacy studies. The results allowed us to state that digital technologies make up the social context of the research participants, and the teachers' lack of digital literacy had negative impacts, since in the period of the COVID-19 pandemic, during emergency remote teaching, digital technology was the main tool used by the category. The teachers' accounts also corroborate that many of them faced many difficulties regarding the use of digital technologies. Although many educational institutions had technological equipment, there were still teachers who made little use of it in their pedagogical practices, which prevented them from improving their digital literacy. Therefore, it is believed that the mastery of digital technologies implies positively in the teaching-learning and interaction process of educators during emergency remote teaching.